Towards the Sustainability of Urban Development - Sztumski, Wiesław (Problemy Ekorozwoju, 2013)
The paper concerns the social ecology of the city. It shows the different types of threats which metropolitan environment creates for citizens: lifestyle, social dissonance, security, management, enslavement, architectural weariness, identity, aesthetics, artificiality, self-government and democracy. Modern cities having certain advantages are also the source of evil. Stopping their further development is impossible, but one must strive to transform them into cities which are really for people. This is a huge challenge for a variety of specialists, also for philosophers. One can realize it, if one harmonizes the structure of the city with its functions and if one respect in the same measure the economic, social and ecological criteria by planning the further development of the cities.